Evaluation of in vitro Anti-Inflammatory Activity of Leaves of Terminalia chebula Retz. (Combretaceae) - Jose, Soumya; Thankappan, Sreeja (Asian Journal of Biological and Life Sciences)
Aim: The present study focused to establish the in vitro anti-inflammatory activity of leaf extracts of Terminalia chebula prepared using different solvents. Materials and Methods: The in vitro antiinflammatory potentiality of leaves of Terminalia chebula were tested using the protein denaturation inhibition assay (bovine serum albumin inhibition assay). Results: Leaves of Terminalia chebula were extracted by ultrasonic assisted extraction using different solvents in increasing order of polarity. The extracts so obtained were screened for anti-inflammatory potential. Leaf extracts of different concentrations ranging from 6.25-100 μg/mL were incubated with bovine serum albumin and its ability to inhibit protein denaturation was measured. The percentage of inhibition of standard diclofenac sodium was determined and its IC50 value was found to be 49.57 μg/ mL. The ethanol, ethanol: distilled water extracts (4:1, 3:2, 2:3, 1:4) and distilled water extracts exhibited greater inhibition of protein denaturation and their IC50 values ranged from 52.03 μg/mL to 77.75 μg/mL. Conclusion: The current study proved that leaves of Terminalia chebula exhibited considerable amount of anti-inflammatory activity and could be used as anti-inflammatory drug but only after proper scientific validation (further in vitro and in vivo studies).
Keywords: Anti-inflammatory study; in vitro study; Protein denaturation assay; Terminalia chebula